HAKIKAT ILMU DALAM ISLAM THE NATURE OF KNOWLEDGE IN ISLAM - Bawadi, Ahmad Jihad; Rahadian, Alip; ., Fadriati; Suryana, Ermis (Jurnal Al-Fatih, 2024)
Islam is a religion that teaches its people to always seek knowledge and a religion that positions science in a very noble position, as a sign of the primacy of science in Islam is the nature of science as a mandatory characteristic of Allah, because all the Prophets and Messengers were sent to teach knowledge to their people , changing life from darkness to bright light, science is the important knowledge that people need to answer all the problems of life in this world and life in the afterlife, talking about knowledge, in the Koran the word science is spread with all kinds of derivatives. The aim of this research is to determine the extent to which the topic is related to current developments so as to produce new knowledge and contribute to knowledge that can be useful. The method used in this research is qualitative with descriptive analysis techniques, namely literature research (library research), namely: a series of activities related to collecting library data, by collecting theories in books such as the Koran, books, articles / journals of expert opinions and other scientific articles that are relevant to this research. The results of this research are: knowing that science consists of a set of knowledge that is used to search, discover and improve understanding of a problem that is being studied using a set of concepts and theories, and by using a set of objective, methodological, scientific methods. Systematic, and universal and the conclusion of this research is what education is like in Islam, the difference between science and knowledge and then what verses talk about science.